1998
DOI: 10.1099/00221287-144-4-1113
|View full text |Cite
|
Sign up to set email alerts
|

Fructose and mannose metabolism in Aeromonas hydrophila: identification transport systems and catabolic pathways

Abstract: Aeromonas hydrophila was examined for fructose and mannose transport systems. A. hydrophila was shown to possess a phosphoenolpyruvate (PEP) :fructose phosphotransferase system (fructose-PTS) and a mannosespecific PTS, both induced by fructose and mannose. The mannose-PTS of A. hydrophila exhibited cross-reactivity with Escherichia coli mannose-PTS proteins. The fructose-PTS proteins exhibited cross-reactivities with E. coli and Xanthomonas campestris f ructose-PTS proteins. In A. hydrophila grown on mannose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Mannans are converted to mannose by endo-and exo-acting mannanases (Centeno et al 2006). The mannose generated is phosphorylated by a transmembrane permease to mannose 6-phosphate (M6P) and then converted by a phosphomannose isomerase to fructose 6-phosphate (F6P) to flow into the Embden-Meyerhof-Parnas (EMP) pathway (Binet et al 1998). Previously, we showed that the gene for BfCE (locus tag BF0774) is located on an operon (locus tags from BF0771 to BF0774) in the B. fragilis NCTC 9343 genome (NC_003228) (Senoura et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mannans are converted to mannose by endo-and exo-acting mannanases (Centeno et al 2006). The mannose generated is phosphorylated by a transmembrane permease to mannose 6-phosphate (M6P) and then converted by a phosphomannose isomerase to fructose 6-phosphate (F6P) to flow into the Embden-Meyerhof-Parnas (EMP) pathway (Binet et al 1998). Previously, we showed that the gene for BfCE (locus tag BF0774) is located on an operon (locus tags from BF0771 to BF0774) in the B. fragilis NCTC 9343 genome (NC_003228) (Senoura et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose to whole cells of P. shigelloides resulted in the formation of C2-labeled ethanol, C3-labeled lactate, C2-labeled acetate and C2-labeled and C3-labeled succinate. This labeling pattern confirms that glucose is converted via the Embden±Meyerhof pathway [9].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane and cytoplasmic fractions were prepared as described previously [5]. PTS activities were assayed by measuring the phosphoenolpyruvate-dependent phosphorylation of a-[ ).…”
Section: Complementation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally established that mannose residues are phosphorylated by a transmembrane permease to mannose 6-phosphate and then converted to fructose 6-phosphate by an intracellular phosphomannose isomerase (Binet et al, 1998). This is surprising, considering the detailed information that is available on the hydrolysis of plant cell wall polysaccharides.…”
Section: Introductionmentioning
confidence: 99%